Integrating EMS and P2 to manage environmental costs and liabilities. (1st January 2003) - Bendavid-Val, Avrom; Cheremisinoff, Nicholas P.
The necessarily similar structures of EMSs and P2 programmes make it possible to integrate the elements of a P2 program smoothly into an EMS. When this is done, P2 is raised from being a mere commitment within the EMS to being a major operational component of the EMS. Instead of looking just at the regulatory compliance status and environmental aspects of your company's operations and then at ways to improve on these, you would also be specifically and systematically looking for high-return P2 opportunities from the outset and doing so continuously. This article provides a fresh look at how an EMS and P2 should work and for the first time provides the basis of an integrated management model for companies.